Distribution of salinity in irrigated soils in the area of the Sarpinskaya hollow in the Caspian lowland - E. I. Kravchenko; N. B. Khitrov; I. N. Gorokhova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The current state of salinity of irrigated soils in the area of the Sarpinskaya hollow in the Caspian lowland has been studied, using the example of the Duboovrazhny irrigated plot in the Volgograd region. At the peak of irrigation in the 85-90s of the last century, forage grasses were cultivated on the plot, irrigation was carried out by sprinkler irrigation, the groundwater level remained satisfactory, and there were no foci of secondary soil salinization. Currently, the plot is a private farm, where melons and vegetables are grown using drip irrigation, the groundwater level remains satisfactory with local formation of temporal water saturated layer. To identify the features of the process of salinization in irrigated soils in the Sarpinskaya hollow based on the materials of the field work performed in 2018–2019, a model of two-dimensional distribution (depth, distance) of the activity of ions (Ca2+, Cl–, Na+) over several profiles along weakly concave low ranges and elongated hollows between them and across relief wave was created. It was revealed that natural soil salinization predominates in the study plot mainly deeper than 1 m, and results from shallow bedding of Khvalynian chocolate clays at ranges. Solonchakous soils occur in elongated hollows between ranges where surface and subsurface runoff water is accumulated and natural drainability is low. Residual traces of soil secondary salinization expressed in the presence of calcium chloride in the soil solution were found. The maximum values of salts and exchangeable sodium are concentrated in the deeper part of the soil profile.